Оценки количества информации в вероятностной модели кодирования изображений - Тырыгин, И.Я. (Український математичний журнал, 1995)
Одержані оцінки зверху на кількість інформації у функціональних класах з первісною невизначеністю, аналогічних класам зображень з обмеженою дисперсією. Використовується ймовірнісна модель теорії інформаційної складності. На відміну від класів KHα0, виявляється, що за даних умов метод типу диференціальної імпульсно-кодової модуляції не дає виграшу відносно детерміністського випадку. Upper bounds are obtained for the amount of information in functional classes with initial uncertainty. These classes are similar to the classes of images with bounded variance. We use the probability model of the theory of information complexity. Unlike the case of classes KHα0 , it turns out that, in this case, the method of differential pulse-code modulation does not give any advantage as compared to the deterministic case.